The Techno-Oligarchic Communication Paradox: Corporate Media Effects and Democratic Deficit in Indonesian Political Parties - Rachmat Hidayat; Pritha Ayodya; Mochamad Husni; Ressa Uli Patrissia; Prasetya Yoga Santoso (Greenation International Journal of Law and Social Sciences, 2026)
Indonesian political parties exhibit a persistent democratic contradiction: electoral turnout above 79% coexists with party trust at only 35%, while algorithmic media ecology has simultaneously enabled civic mobilization and reinforced oligarchic entrenchment. Drawing on a qualitative constructivist design integrating PRISMA-guided systematic literature review (N = 44 studies, 2019–2025), single-case study of the Perindo Party, and systematic social media content analysis (N = 400 posts, κ = 0.81), this study extends Aeron Davis's (2019) four-phase media effects model through the proposed Techno-Oligarchic Communication Paradox (TOCP) framework. TOCP formalizes three structural mechanisms—Funding Corporatocracy, Digital Personalization Without Participation, and Algorithmic Legitimation Substitution—that explain how Phase 4 digital communication technologies paradoxically deepen democratic deficits within oligarchic institutional logics. Perindo's deployment of MNC Group infrastructure (68% corporate content), figure-centric microtargeting (79% HT-branded), and high algorithmic reach (34% youth) produced comprehension failure (72% unable to identify party platform) and legitimacy decline (−21 points in trust; electability at 4.1%). TOCP advances Davis's framework by centering corporate media ownership as an organizing structural variable applicable to emerging democracies in which media–party fusion is constitutive of the political communication landscape.